2010
DOI: 10.1158/1940-6207.capr-09-0201
|View full text |Cite
|
Sign up to set email alerts
|

Serum Oxidized Protein and Prostate Cancer Risk within the Prostate Cancer Prevention Trial

Abstract: To evaluate the role of oxidative stress in prostate cancer risk, we analyzed serum levels of protein carbonyl groups in 1,808 prostate cancer cases and 1,805 controls, nested in the Prostate Cancer Prevention Trial, a randomized, placebo-controlled trial that found finasteride decreased prostate cancer risk. There were no significant differences in protein carbonyl levels in baseline samples between those later diagnosed with prostate cancer and those without at the end of study biopsy. Adjusted odds ratios a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Sample sizes ranged from 15 to 3,163. 31 , 32 The mean age of participants ranged from 60 years to 74 years. Twenty-three studies were conducted using a case control study design, 19 were case control studies, two were prospective, one was nested, and one was a subset of the Nashville Men's Health study.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 15 to 3,163. 31 , 32 The mean age of participants ranged from 60 years to 74 years. Twenty-three studies were conducted using a case control study design, 19 were case control studies, two were prospective, one was nested, and one was a subset of the Nashville Men's Health study.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, by the TNF-α/AP-1 transduction pathway and the NF-κB-Inducing Kinase (NIK) transduction pathway, the local production of proinflammatory cytokines [34] is determined by triggering apoptotic pathway which limits uncontrolled cell proliferation. In this regard, TR10/P3795 exerted a significant reduction of MDA and inflammatory markers unlike finasteride which had already been demonstrated not to affect protein oxidation in the prostate [35]. This is likely to be advocated for by the total phenolic content of a selected extract from pumpkin in its composition.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the protein carbonyl levels in tissue were significantly higher in HGPIN than those in malign Ca. Some studies have provided conflicting evidence on the association between protein oxidation and cancer risk, with positive results for Hodgkin's lymphoma and bladder cancer, but not for lung or brain cancer [41]. However, Hoque et al [41] showed that there were no significant differences in protein carbonyl levels in basaline samples between those later diagnosed with prostate cancer and those without at the end of study biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have provided conflicting evidence on the association between protein oxidation and cancer risk, with positive results for Hodgkin's lymphoma and bladder cancer, but not for lung or brain cancer [41]. However, Hoque et al [41] showed that there were no significant differences in protein carbonyl levels in basaline samples between those later diagnosed with prostate cancer and those without at the end of study biopsy. Neither was there a significant association between protein carbonyl level and risk when analyzing high-grade and low-grade disease separately, nor did finasteride affect protein oxidation levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation